Trois exils, trois femmes, trois Médées du Québec contemporain - Carrière, Marie (Atlantis, 2010)
The myth of Medea makes its contemporary appearance in the feminist writings in Quebec. However, the works in the study need first and foremost to be rewrites of the myth situating the infanticide mother in a very precise social and historical context — namely one of exile and of migration.